A Nonpalpable Nodule in Ectopic Axillary Breast Tissue: Consider Phyllodes Tumor - Eva Ruvalcaba-Limón; Verónica Bautista-Piña; Julio Ramírez-Bollas; Ruby Espejo-Fonseca; Sergio Rodríguez-Cuevas (Hindawi Limited, 2016)
Benign and malignant pathology can develop in ectopic axillary breast tissue, such as fibroadenomas, phyllodes tumors, and breast cancer. We present a rare case of an asymptomatic 43-year-old woman with an axillary nodule which was identified during screening mammography within ectopic axillary breast tissue, initially considered as a suspicious lymph node. Radiologic studies were considered as Breast Imaging-Reporting Data System (BI-RADS) 4. A hyperdense, lobular, and well-circumscribed nodule was identified in mammogram while the nodule by ultrasound (US) was hypoechoic with indistinct microlobular margins, without vascularity by Doppler, and measuring 1.26×1 cm. Core-needle biopsy reported a fibroepithelial neoplasm. The patient was submitted to local wide-needle excision located in intraoperative radiography of the surgical specimen and margin evaluation. Final histopathological study reported a 1.8×1.2 cm benign phyllodes tumor, with irregular, pushing, and clear wide margins within normal ectopic breast tissue. The patient without surgical complications continued annual screening without recurrence during a follow-up that took place 24 months later.